Tamoxifen Attenuates Lipopolysaccharide/Galactosamine-induced Acute Liver Failure by Antagonizing Hepatic Inflammation and Apoptosis. (3rd April 2017) - Zhang, Peng; Zhang, Meisheng; Wan, Mengqi; Huang, Xiaoliu; Jiang, Yan; Xu, Siying; Luo, Mansheng
ABSTRACT: Bacterial lipopolysaccharide (LPS)-induced acute liver failure (ALF) is a common severe clinical syndrome in intensive care unit. No other methods are available for its prevention apart from supportive treatment and liver transplantation. Tamoxifen (TAM) was reported to attenuate ALF induced by excessive acetaminophen, while its effect on LPS-induced ALF remained unknown. For this, in the present study, we comprehensively assessed whether TAM can attenuate ALF induced by LPS/galactosamine (GaIN). Mice were given TAM once a day for three times. Twelve hours after the last treatment, mice were given LPS/GaIN (intraperitoneally [i.p.]). Survival, plasma transaminases, and histopathology were examined. Serum TNF-α and IL-1β were analyzed by ELISA. Hepatic apoptosis was analyzed by TUNEL and caspase-3 Western blotting, respectively. Compared to the model group, ALF induced by LPS/GaIN was alleviated remarkably following TAM administration, as evidenced by the improvement of survival (87.5% vs. 37.5%), hepatic swell, moderate transaminases, slightly increased serum TNF-α, IL-1β ( P < 0.05), and moderate histopathology. In respect of apoptosis, severe hepatocellular apoptosis was reduced notably by TAM treatment confirmed by less TUNEL-positive hepatocytes and decreased caspase-3 cleavage. The results demonstrated that TAM could attenuate LPS/GaIN-induced ALF effectively, probably due to hepatic inflammation and apoptosis antagonism. Furthermore, it was the first report about the effect of TAM on LPS/GaIN-induced ALF.